Effectiveness of The Utilization of Transformative Learning Process on Developing Creative Thinking Abilities among Student Leaders - Phromjuang, Kornwika; Leaudnakrob, Napadon; Poltana, Pisit; Chaiwut, Pongpinit; Yingyoud, Paradorn; Saeio, Kiattisak (NU Journal of Nursing and Health Sciences, 2020)
Transformative learning process based on Mezirow’s theory was utilized to promote student leaders for developing creative thinking. This research aimed to 1) study the level of creative thinking abilities among student leaders by utilizing on transformative learning process after participating in the "Student development activities in the 21st century" project, 2) explore the level of student leaders’ opinion on the activities of the Project, and 3) discover lived experiences among student leaders after participating in the Project. Mixed methods were done. Purposive sampling was applied for the quantitative study. Subjects were freshmen (n = 70) who are student leaders, studying at Boromarajonani College of Nursing, Sirindhorn College of Public Health, and Abhaibhubejhr College of Thai Traditional Medicine Prachinburi under Praboromarajchanok Institute, and participating in the Project at Westgate Residence Hotel, Nonthaburi Province. The qualitative study (n = 30) was applied to understand lived experiences among student leaders after participating in the Project. Personal interview was performed by using on in-depth interview and focus groups were implemented with semi-structured interviews. Snowball sampling techniques were applied on this study. Questionnaires composed of two components; the creative thinking abilities questionnaire and the student leaders’ opinion on this Project questionnaire. Content validity was investigated by using the Index of Item Objective Congruence that placed on the good level (0.70-1.00). Analyses of creative thinking abilities and student leaders’ opinion after participating in transformative learning process were performed on Mean ( ) and Standard Deviation (S.D.). For the qualitative study, thematic analysis and major themes were synthesized. Findings revealed that after participating in this Project for overall, creative thinking abilities among leader students were scored at the high level ( = 4.12, S.D. = 0.72). Student leaders’ opinion was also placed at the highest level ( = 4.26, S.D. = 0.67). The student leaders had higher positive outcomes on creative thinking abilities. Three thematic analyses that emerged from the data were: 1) practiced mindfulness and thought more fluently, 2) learned to think outside the box, think flexible, and think thoroughly, and 3) performed a systematic analysis of thinking and practiced reflection. Therefore, this project activity should be organized at least once a year to encourage student leaders to be more creative.